If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -4) + -1(2x + -4) = 0 Reorder the terms: 2(-4 + 3x) + -1(2x + -4) = 0 (-4 * 2 + 3x * 2) + -1(2x + -4) = 0 (-8 + 6x) + -1(2x + -4) = 0 Reorder the terms: -8 + 6x + -1(-4 + 2x) = 0 -8 + 6x + (-4 * -1 + 2x * -1) = 0 -8 + 6x + (4 + -2x) = 0 Reorder the terms: -8 + 4 + 6x + -2x = 0 Combine like terms: -8 + 4 = -4 -4 + 6x + -2x = 0 Combine like terms: 6x + -2x = 4x -4 + 4x = 0 Solving -4 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 0 + 4 4x = 0 + 4 Combine like terms: 0 + 4 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| 45-23=x | | 25x-30x-16=0 | | -16-9-2= | | 4(x+15)=17x | | -4y+8=5y+9 | | -4(-2+5)= | | 5t^2+14x+3=0 | | 6y+8y=98 | | 15+2(9-6)+9= | | 5x-y+15=0 | | 15+2(9-6)-9= | | x-15=-4 | | -18+12+-6= | | -9(3b+1)+(28b-9)=0 | | (-18)(12)(-6)= | | 5p-6(p-5)+5(q-5)= | | 3(-6)(4)(-2)= | | (6u^3)(-5u^7v^6)= | | 3(-6)(4)(-2)=(-18)(12)(-6) | | 18=6x | | 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 |